Analisis Kepuasan Pengguna Aplikasi iRiau Menggunakan Metode EUCS dan TAM - Praniffa, Anisya Caty; Ahsyar, Tengku Khairil; Jazman, Muhammad; Syaifullah; Marsal, Arif (AI Society & STMIK Indonesia, 2025)
iRiau is a digital platform that makes it easier for people to access the Soeman HS library. User satisfaction assessments are made to access the extent of iRiau application being relevant and effective. The study use the EUCS and TAM methods to identify factors affecting user satisfaction. The study sample involved 125 analyzed respondents using SPSS. According the research, five of the seven hypotheses tested were accepted. Variable Perceived Usefulness, Content, Accuracy, Format, and Timeliness significantly impact user satisfaction. However, variables of Perceived of Use and Ease of Use are insignificant. Variables with the most significant influences are Perceived Usefulness and Timelliness. The linar regression model produces an R-Square of 0.959, showing that such independent variables explain 95.9% of user satisfaction.